2015
DOI: 10.5114/hpr.2016.54545
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and the risk of mental health disorders during adolescence

Abstract: <b> Background</b><br /> Attachment is one of the more important developmental aspects for predicting a person’s level of adaptation and mental health. Previous research in this area suggests a relationship between insecure attachment and behavioural disorders, deviations as well as depression and other affective disorders. The goal of this study was to determine the relationships between adolescents’ attachment patterns and aggression as well as internalisation and externalisation of problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The current findings are consistent with a number of lines of research. The findings complement studies showing that TBSO by adolescents from the community is associated with higher levels of mentalization, higher levels of communication with parents, lower levels of aggression, higher levels of psychological well-being, lower levels of internalized maladjustment and lower levels of alienation [33][34][35][36]. The current findings are compatible with research showing that trust beliefs in others buffers the effects of social stress on the mental health and health for adolescents from the community [3,4].…”
Section: Discussionsupporting
confidence: 88%
“…The current findings are consistent with a number of lines of research. The findings complement studies showing that TBSO by adolescents from the community is associated with higher levels of mentalization, higher levels of communication with parents, lower levels of aggression, higher levels of psychological well-being, lower levels of internalized maladjustment and lower levels of alienation [33][34][35][36]. The current findings are compatible with research showing that trust beliefs in others buffers the effects of social stress on the mental health and health for adolescents from the community [3,4].…”
Section: Discussionsupporting
confidence: 88%
“…The study of attachment, an original construct of Bowlby’s (1969) theory, is a valuable theoretical framework to understand the influence of parents and friends on adolescent development and mental health problems such as eating disorders (ED). Recent studies have shown that a failure in the primary bond with the primary attachment figure constitutes both an etiopathogenic and a mental health risk factor for adolescents (Grzegorzewska & Farnicka, 2016). Studies on ED, considering the attachment theory, report that the insecure attachment is the most common parental style among adolescents with ED (Gander et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The period of adolescence is characterized by increased psychosocial opportunities and risks, including heightened vulnerability for the onset of serious mental health conditions such as anxiety and depression [1], psychotic disorders [2], and eating disorders [3]. Researchers have sought to identify factors which might support young people during this period of development, with parent-teen attachment security consistently shown to underpin adolescent wellbeing [4,5].…”
Section: Introductionmentioning
confidence: 99%